2022
DOI: 10.1101/2022.03.29.486252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focal Non-invasive Deep-brain Stimulation with Temporal Interference for the Suppression of Epileptic Biomarkers

Abstract: Neurostimulation applied from deep brain stimulation (DBS) electrodes is an effective therapeutic intervention in patients suffering from intractable drug-resistant epilepsy when resective surgery is contraindicated or failed. Inhibitory DBS to suppress seizures and associated epileptogenic biomarkers could be performed with high-frequency stimulation (HFS), typically between 100 – 165Hz, to various deep-seated targets such as for instance the Mesio-temporal lobe (MTL) which leads to changes in brain rhythms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…As such, the different behavioural and neural effects of striatal tTIS80Hz and tTIS20Hz despite comparable carrier frequencies (centered on 2kHz) indicate that temporal interference was indeed the driving force of the present effects. Moreover, disruption of reinforcement motor learning with tTIS80Hz (relative to tTIS20Hz) was specifically related to neuromodulation of the striatum, where the amplitude of the tTIS field was highest according to our simulations (see 52,94 for recent validations of comparable simulations in cadavers experiments). Hence, we believe that the frequency-and reinforcementdependent tTIS effects reported here cannot be explained by direct modulation of neural activity by the high frequency fields.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As such, the different behavioural and neural effects of striatal tTIS80Hz and tTIS20Hz despite comparable carrier frequencies (centered on 2kHz) indicate that temporal interference was indeed the driving force of the present effects. Moreover, disruption of reinforcement motor learning with tTIS80Hz (relative to tTIS20Hz) was specifically related to neuromodulation of the striatum, where the amplitude of the tTIS field was highest according to our simulations (see 52,94 for recent validations of comparable simulations in cadavers experiments). Hence, we believe that the frequency-and reinforcementdependent tTIS effects reported here cannot be explained by direct modulation of neural activity by the high frequency fields.…”
Section: Discussionmentioning
confidence: 57%
“…The second key element consists in applying a small difference of frequency between the two alternating currents. The superposition of the electric fields creates an envelope oscillating at this low-frequency difference, which can be steered towards individual deep brain structures (e.g., by optimizing electrodes' placement), and is in a range able to influence neuronal activity 40,[50][51][52] . An interesting feature of tTIS is to stimulate at a particular frequency of interest in order to preferentially interact with specific neuronal processes 40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Safe optimization could also be applied further to safely guide the use of novel stimulation and recording paradigms. [39][40][41] Ultimately, all of these approaches will be critical for developing safe and effective automatic optimization approaches for neuromodulation.…”
Section: Future Workmentioning
confidence: 99%
“…Five studies were conducted to evaluate the effects of TI on human behavioral or neurophysiological function. In neurophysiological investigation, Acerbo et al (2022) used stereoelectroencephalography electrodes to compare electric field distributions in the brains of two cadavers during TI stimulation and tACS. This study measured brain discharge by implanting 12 stereoelectroencephalography electrodes in the temporal lobe on both sides and concluded that 130 Hz TI better penetrated the human hippocampus than the 130 Hz tACS.…”
Section: Human Studiesmentioning
confidence: 99%